Ben Franklin's almanac : being a true account of the good gentleman's life - Fleming, Candace (Atheneum Books for Young Readers, 2003)
Brings together eighteenth century etchings, artifacts, and quotations to create the effect of a scrapbook of the life of Benjamin Franklin.